MON-385 Insulin Resistance and Osteoporosis in People Living with HIV - Premaor, Melissa Orlandin (J Endocr Soc, 2020)
The life expectancy of people living with HIV (PLHIV) increased considerably after the advent of antiretroviral therapy (ARV). Nowadays, it is almost the same as the general population. However, this increase in survival exposes PLVH to age-related morbidities, including chronic metabolic and bone diseases. PLHIV has a low bone mineral density (BMD) and a high prevalence of osteoporosis. Moreover, the frequency of diabetes mellitus (DM) seems to be twice the frequency of the general population. Insulin resistance and DM might be associated with bone diseases in PLHIV. Our study aim was to evaluate the association between insulin resistance and osteoporosis in PLHIV. We carried out a cross-sectional study at the municipality of Santa Maria, South Brazil. PLHIV age 50 yrs or over on treatment with ARV were included. All subjects registered to receive ARV in the university hospital during the period 2016 to 2018 were invited to participate. Those who accepted responded to a standardized questionnaire, performed a bone density scan and a lateral spinal X-ray, underwent peripheral blood collection, and had their weight and height measured. Insulin resistance was considered present when HOMA-IR> 2.7 (Gelonese, 2009). The TyG index was also calculated (VASQUES, 2011). Of the 101 PLHIV who agreed to participate, 84 underwent both insulin and BMD measurements. The prevalence of osteoporosis was 19%. Vertebral fractures were twice as frequent in individuals with osteoporosis (73.3% vs. 36.5%, p = 0.018). Participants with osteoporosis had lower BMI and triglyceride values than those without it. The frequency of insulin resistance calculated by HOMA-IR was 68.2%, and it was associated with glucocorticoid use, smoking, and BMI. HOMA-IR [4.8(6.6) vs. 8.68(9.6), p =0.013], and TyG [5.0(0.3) vs. 5.2 (0.4), p=0.029] mean values were lower in the group with osteoporosis; however, this association disappeared after correction for BMI in the logistic regression model. In conclusion, in our study, PLHIV with osteoporosis have lower insulin resistance than PLHIV without it. Nevertheless, this finding appears to be relating to a lower BMI. Further studies are needed to assess the effect of insulin resistance on fracture risk in PLVH. GELONEZE, B. et al. HOMA1-IR and HOMA2-IR indexes in identifying insulin resistance and metabolic syndrome: Brazilian Metabolic Syndrome Study (BRAMS). Arq Bras Endocrinol Metabol. 2009 Mar;53(2):281-7 VASQUES, A. C. et al. Análise Crítica do Uso dos Índices do Homeostasis Model Assessment (HOMA) na Avaliação da Resistência à Insulina e Capacidade Funcional das Células-C Pancreáticas. Arq. Bras. Endocrinol. Metab., 2008;52/1:32-39.